THE ANALYSIS OF DEATH THEME IN “THE FAULT IN OUR STAR” STORY BY JOHN GREEN - Syielvi Dwi Febrianty; Tomi Arianto; Nitasri Murawaty Girsang; Mirda Aryadi (IdeBahasa, 2023)
This research aimed to reveal the phenomenon of death in literary work. The theme of death is sometimes ignored by literary critics because it is often seen as a spice in the story. In fact, the narrative of death has a very significant that determines the plot in the story. Ross (2009) a French psychologist put forward the theoretical concept of this phenomenon with the theory of death and dying. Psychologically, there are several stages that are experienced by people who are facing terminal illness or people who are left behind in the face of death. Departing from several conceptual deaths, the researchers determined the research data source in the form of a story by John Green entitled "The Fault in Our Stars". This phenomenal story is very well known among teenagers and has even been encrypted in the form of a movie. This story received various awards both in the form of a printed narrative and after being filmed. The story of this story is dominated by teenage romance and the struggle with cancer. However, it is interesting to study how the attitude of the people around them, including the main characters in dealing with death. By using Kubler Ross theory, there are two variables that would be found. First, the phenomenon of death and dying as the general perception in dealing with death and dying reflected in the story The Fault in Our Stars . Second, the psychological stages experienced by the character in facing death in the story.